PENGARUH TINGKAT KEKERUHAN PERAIRAN TERHADAP KOMPOSISI SPESIES MAKRO ALGAE KAITANNYA DENGAN PROSES UPWELLING PADA PERAIRAN RUTONG-LEAHARI - Modesta R. Maturbongs (Universitas Musamus, Merauke, Papua, 2015)
This study aims to determine the relationship of turbidity levels of Rutong – Leahari waters with macro algae species composition relation to the upwelling process .This research was conducted at the end of April to August 2011 at the Rutong and Leahari village waters. The method used is the line transect method ( line -transect method) combined with the quadrant method. Data were analyzed using two-way ANOVA analysis, t-test and correlation. The results showedturbiditylevels of Rutong.Leahari waters is very highonthe pre-upwelling conditions, butthe results of the analysiss howedturbidity levelsin the Leahari-Rutong waters is not significantly different between conditionspre-upwelling and upwelling. Instead turbidity level changes between the conditions of pre-upwelling and upwelling influence on the presence of other types of macro algae, as shown by the large number of types of algae found in upwelling conditions than pre-upwelling conditions.